Growing duckweed for biofuel production: a review. (1st July 2014) - Cui, W.; Cheng, J. J.
Abstract: Duckweed can be utilised to produce ethanol, butanol and biogas, which are promising alternative energy sources to minimise dependence on limited crude oil and natural gas. The advantages of this aquatic plant include high rate of nutrient (nitrogen and phosphorus) uptake, high biomass yield and great potential as an alternative feedstock for the production of fuel ethanol, butanol and biogas. The objective of this article is to review the published research on growing duckweed for the production of the biofuels, especially starch enrichment in duckweed plants. There are mainly two processes affecting the accumulation of starch in duckweed biomass: photosynthesis for starch generation and metabolism‐related starch consumption. The cost of stimulating photosynthesis is relatively high based on current technologies. Considerable research efforts have been made to inhibit starch degradation. Future research need in this area includes duckweed selection, optimisation of duckweed biomass production, enhancement of starch accumulation in duckweeds and use of duckweeds for production of various biofuels.